Porównanie procesu wyłuszczania nasion sosny zwyczajnej (Pinus sylvestris L.) z szyszek całych i pozbawionych trzpienia - Aniszewska, Monika (Leśne Prace Badawcze, 2012)
The article describes seed extraction from Scots pine cones from the Złoczew Forest District (Regional Directorate of the State Forests in Łódź). The studied cones were divided into two groups. One group contained whole cones, while the other contained cones with their stem drilled out. In order to compare the seed extraction process, both groups were dried at the same time (for 10 hours) and at the same temperature and humidity (temperature: 35°C for the first two hours, 50°C afterwards, humidity: 33% then 7.3%). It was assumed that drilling the stems out of cones would cause them to open faster and allow for quicker seed harvesting. This hypothesis was not supported, as the drilled cones did not open quicker, therefore the cone drilling procedure was ineffective, at least for cones of the origin studied. On average the cones took 7.59 h to open (7.51 h for whole cones and 7.68 h for drilled cones). The harvested seeds were classified as Grade 1, indicating that they were extracted under the correct conditions.